Biodegradable Films: Microporous Biodegradable Films Promote Therapeutic Angiogenesis (Adv. Healthcare Mater. 17/2020). Issue 17 (9th September 2020) - Hendow, Eseelle K.; Moazen, Mehran; Iacoviello, Francesco; Bozec, Laurent; Pellet‐Many, Caroline; Day, Richard M.
Abstract : In article number 2000806 by Richard M. Day and co‐workers, highly porous biodegradable films are prepared using thermally‐induced phase separation. In vivo implantation of the films into ischemic tissue stimulates increased expression of pro‐angiogenic growth factor genes. This provides a favourable local environment for neovascularization, increased tissue perfusion, and therapeutic angiogenesis in ischemic tissue. The findings pave the way to establishing new materials‐based strategies to achieve therapeutic angiogenesis.